2013
DOI: 10.5005/jp-journals-10019-1116
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Combined Width of Maxillary Anterior Teeth, Interpupillary Distance and Intercommissural Width in a Group of Indian People

Abstract: Purpose:The objective was to evaluate the correlation between the width of distal surface of canine (CWC), interpupillary distance (DMP) and intercommissural width (DCM) in a group of central Indian people. Materials and methods:A total of 540 central Indian subjects (277 males and 263 females) aged 19 to 30 years were selected. DMP and DCM were measured on subject's face using digital vernier caliper [Mitutoyo (UK) Ltd.] with precision of 0.01 mm. Irreversible hydrocolloid impression of the upper arch was tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…This is proportional to study that is conducted by Hussain et al 23 which stated intercommissural width toward intercanine width was not significant and weakin negative direction. The research conducted by Deogade et al 24 suggested that substantial relationship between intercommissural width against mesiodistal width of the maxillary anteriorteeth are not significant and weak in negative direction is also comparable to this study.…”
Section: Original Researchsupporting
confidence: 89%
“…This is proportional to study that is conducted by Hussain et al 23 which stated intercommissural width toward intercanine width was not significant and weakin negative direction. The research conducted by Deogade et al 24 suggested that substantial relationship between intercommissural width against mesiodistal width of the maxillary anteriorteeth are not significant and weak in negative direction is also comparable to this study.…”
Section: Original Researchsupporting
confidence: 89%
“…Most studies[192021] have suggested that skull anthropometry can be a primary starting point in selecting the mesiodistal width of the maxillary anterior teeth. [1314] Most studies[151617] done in this area also have been carried out to study the stature[22232425] and personality assessments based on anthropometric values. However, these do not include Asia and India even though they form largest population as compared to other ethnic groups; no measurements of tooth sizes have been made on the Central Indian population.…”
Section: Discussionmentioning
confidence: 99%
“…After recording the demographic information such as age and sex of each participant, various craniometric and odontometric measurements were obtained with the help of a nonstretchable measuring tape, a spreading caliper, and a sliding digital stainless steel Vernier caliper, as suggested in the previous studies. [13141516]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations